Agriculture and climate change: The important role of extension systems - Davis, Kristin E. (International Food Policy Research Institute, 2009)
Climate change will certainly affect agriculture, but agriculture can also be harnessed to mitigate greenhouse gas (GHG) emissions. A key element in supporting agriculture’s role is information. The costs of adapting agriculture to climate change can be large and the methods not always well known. Mitigation efforts will require information, education, and technology transfer. Agricultural extension and advisory services, both public and private, thus have a major role to play in providing farmers with information, technologies, and education on how to cope with climate change and ways to contribute to GHG mitigation. This support is especially important for resource-scarce smallholders, who contribute little to climate change and yet will be among the most affected. Support from extension for farmers in dealing with climate change should focus on two areas: adaptation and mitigation, explained below. But first, it is important to define extension.